Behaviour of thermolabile materials in microwave vacuum dehydration - Taib, Mohd. Rozainee (Faculty of Chemical and Natural Resource Engineering, 2009)
The objectives of this research were; 1) to design and develop a laboratory scale microwave vacuum dehydration testing rig for drying of thermolabile materials; 2) to study the drying mechanism of thermolabile material; 3) to determine the kinetics of microwave energy transfer in a vacuum testing rig. A laboratory-scale microwave vacuum dehydration system was successfully developed for dehydration of thermolabile materials. Microwave is recognized as a fast heating process characterised by volumetric heating. Contrary to conventional dehydration method which heats from the surface of material, microwave heats material from inside out. Incorporation of vacuum enhances the microwave dehydration process by allowing water to vaporize at lower temperature. Thus, dehydration of thermolabile materials can be achieved at low temperature and shorter time thereby preventing degradation of nutritional values and texture. Behaviours of thermolabile materials such as jackfruit, guava and papaya in microwave vacuum dehydration were studied. Operating parameters such as microwave power and vacuum pressure were found to influence the dehydration process. Increment of microwave power resulted in higher drying rates but increased risks of charring. However, the charring could be reduced with combination of microwave power. Products dried by combination of microwave power has lesser shrinkage and softer texture due to porous (puffing) structure induced by vacuum condition. It also possessed better reconstitution ability. In addition, papaya dried using microwave vacuum was found to have high enzyme activity retained.